Audio technology and mobile human-computer interaction: from space and place, to social media, music, composition and creation - Chamberlain, Alan; Bødker, Mads; Hazzard, Adrian; McGookin, David; De Roure, David; Willcox, Pip; Papangelis, Konstantinos (IGI Global, 2017)
Audio-based mobile technology is opening up a range of new interactive possibilities. This paper brings some of those possibilities to light by offering a range of perspectives based in this area. It is not only the technical systems that are developing, but novel approaches to the design and understanding of audio-based mobile systems are evolving to offer new perspectives on interaction and design and support such systems to be applied in areas, such as the humanities.